Exploring Higher Education EFL Students’ Perception of AI Writing Tools in the 5.0 Era - Safitri, Muliana; Fithriani , Rahmah (Jayapangus Press, 2024)
This study explores the perceptions of English as a Foreign Language (EFL) students in higher education regarding artificial intelligence writing tools (AIWTs) in the context of Era 5.0. The research aims to understand how AIWTs influence writing quality, efficiency, and creativity among EFL students. Employing a mixed-methods approach, it examines the types of AIWTs used, students' perspectives on their benefits and drawbacks, and the overall value they bring to EFL writing. A total of twenty students from the English education study program at the State Islamic University of North Sumatra, Medan, participated in an online questionnaire aimed at investigating their perceptions on the use of AIWTs in Era 5.0. The findings highlight that EFL students perceive AIWTs as beneficial for enhancing writing quality, speeding up the writing process, and fostering creativity. However, concerns about potential limitations on creativity are also expressed. Despite this, AIWTs are generally regarded as valuable tools for EFL students in higher education. The study offers a reasonable strategy for using AIWTs to guarantee academic performance while maintaining writing creativity.